PENGARUH CURRENT RATIO, RETURN ON ASSETS, DAN DEBT TO EQUITY RATIO TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR KONSTRUKSI NON BANGUNAN YANG TERDAFTAR DI BEI PERIODE 2018 – 2022 - Putri, Fitriani Ade; Amelia, Rizka Wahyuni (Journal of Research and Publication Innovation, 2024)
This study aims to examine the influence of Current Ratio, Return On Assets, and Debt To Equity Ratio on Financial Distress in Non-Building Construction Sub-Sector Companies listed on the Indonesia Stock Exchange (BEI) during the period 2018-2022. The method used is quantitative. The results of the F-test show that the variables Current Ratio, Return On Assets, and Debt To Equity Ratio collectively have a significant influence on Financial Distress at a significance level of (0.000000 < 0.05). The T-test results indicate that Current Ratio significantly affect Financial Distress with a value of (0.0000 < 0.05). However, the Return On Assets variable shows a p-value of (0.4478 > 0.05), indicating no significant influence on Financial Distress. Similarly, the Debt To Equity Ratio variable shows a p-value of (0.4985 > 0.05), suggesting no significant influence on Financial Distress. The Adjusted R Square of 0.905 indicates that the combined contribution of the variables significantly affects the dependent variable by 90.5%, with the remaining 9.5% influenced by factors outside the scope of this study.